Strategi Komunikasi Kelembagaan Digital pada Subbagian Hubungan Lembaga Negara/Pemerintah di BPK RI - Kayla Qathrunnada Khairunnisa; Amiruddin Saleh (Jurnal Kajian dan Penelitian Umum, 2026)
This study examines the digital institutional communication strategy of the State/Government Institution Relations Sub-division of the Supreme Audit Institution (BPK RI) using a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and document analysis to understand the implementation of digital transformation in inter-organizational communication practices. The findings show that BPK RI’s digital transformation has developed incrementally and is guided by the BPK RI Strategic Plan 2025–2029. This transformation is implemented through several official digital platforms, including JASMIN, SIMoU, the Bakohumas Forum, and the Hublem Forum, which operate within a structured and hierarchical coordination system across institutions. Supporting factors for this transformation include adequate technological infrastructure, strong leadership commitment, and increasingly competent human resources in digital skills. However, the study also identifies key barriers, such as network instability in certain regional areas and disparities in digital literacy among institutions. These challenges are addressed through adaptive strategies that highlight the role of boundary spanners in bridging communication gaps between organizational actors and digital systems. Overall, the integration of digital communication within BPK RI has significantly improved coordination efficiency, organizational responsiveness, and transparency of information to stakeholders. This progress supports the broader agenda of digital-by-default governance in public sector administration.